Disease-modifying osteoarthritis drugs (DMOADs): new trends in osteoarthritis therapy - O. A. Shavlovskaya; О. А. Gromova; A. Yu. Kochish; Yu. D. Yukhnovskaya; I. D. Romanov; I. A. Bokova (Фармакоэкономика)
The review examines pharmacological agents that can have potential disease-modifying osteoarthritis drugs (DMOADs) status. DMOADs prevent the progression and further structural joint damage (structure-modifying effect), leading to a decrease in symptoms severity (symptom-modifying effect), such as pain, and improvement of joint function. Approaches to potential DMOADs selection are discussed: (1) the preferred target (bone, cartilage, synovia); (2) action drug mechanism/anti-cytokine therapy (matrix metalloproteinase inhibitors, inhibitors of pro-inflammatory interleukins, etc.). The main delivery systems of drugs claiming to be of DMOADs status and possible contribution of immunological mechanisms to osteoarthritis pathogenesis are considered. Methods evaluating the effectiveness of DMOADs therapy are of great interest (cytology, microscopy, radiological research methods, blood and synovia biochemical markers). Based on research results analysis, the following substances can be considered as potential DMOADs: chondroitin sulfate, glucosamine sulfate, undenatured type II collagen, vitamin D. Each of them has symptom-modifying and structural-modifying effects.